4
$\begingroup$

Given positive integers $n$ and $k$, ($1\leqslant k\leqslant n-1$), and a real constant $s\in(0,1)$, I'm considering the following summation: $$\sum_{i=0}^{n-k}(-1)^i\binom{n-k}{i}(k+i)^s$$ My goal is to show that this summation, for any choice of $n$ and $k$, is negative. Can anyone give me some possible directions to think about? Thanks!

$\endgroup$
  • $\begingroup$ This sum seems very similar to Stirling Numbers of the Second Kind, with the exception that you have $(k+i)$ instead of $(k-i)$: mathworld.wolfram.com/StirlingNumberoftheSecondKind.html Maybe one approach would be to expand $(k+i)^s$ as a binomial, and then re-express the sum in terms of a summation of Stirling Numbers. The other option would be to write out the sum in terms of a hypergeometric function and then use related identities to massage the result. Does your summation come from something combinatorial? $\endgroup$ – Alex R. Jun 15 '17 at 21:17
  • $\begingroup$ Thanks for the information! The summation comes from some intermediate results of order statistics of Weibull distribution. It does not have a very nice combinatoric intuition - it just ended up in this format algebraically. I will look into the Stirling Numbers and hypergenmetric function that you mentioned. Can you say a bit more about "expanding $(k+i)^s$ as a binomial"? $\endgroup$ – user3026001 Jun 16 '17 at 0:54
3
$\begingroup$

Here is a possible direction of approach.

Lemma. If we denote the function $$f(n,k):=\sum_{i=0}^{n-k}(-1)^i\binom{n-k}i(k+i)^s,$$ then $f(n+1,k+1)-f(n,k)=-f(n+1,k)$.

Proof. Consider the difference $f(n+1,k)-f(n,k)$ instead: \begin{align} f(n+1,k)-f(n,k) &=\sum_{i=0}^{n+1-k}(-1)^i\binom{n+1-k}i(k+i)^s- \sum_{i=0}^{n-k}(-1)^i\binom{n-k}i(k+i)^s \\ &=(-1)^{n+1-k}(n+1)^s+\sum_{i=0}^{n-k}(-1)^i\binom{n-k}i \frac{i\,(k+i)^s}{n+1-k-i} \\ &=(-1)^{n+1-k}(n+1)^s+\sum_{i=0}^{n-k}(-1)^i\binom{n-k}{i-1}(k+i)^s \\ &=-(-1)^{n-k}(n+1)^s-\sum_{j=0}^{n-k-1}(-1)^j\binom{n-k}j(k+1+j)^s \\ &=-\sum_{j=0}^{n-k}(-1)^j\binom{n-k}j(k+1+j)^s \\ &=-f(n+1,k+1). \end{align} The proof follows. $\square$

Now, one may proceed with some induction on $n$ and for all $1\leq k<n$. You see, if $f(n+1,k)<0$ then $f(n+1,k+1)>f(n,k)$. The following fact can be brought to bear: whenever $d<m$, $$\sum_{i=0}^m(-1)^i\binom{m}ii^d=0.$$

Next, try to convince yourself that for fixed $k$: $$\lim_{n\rightarrow\infty}f(n,k)=0.$$ This statement and the above lemma (and remark) would allow the conclusion you desire.

$\endgroup$
7
$\begingroup$

For a function $f(x)$, and a non-negative integer $m=n-k$, the expression $\Delta_mf(x)=\sum (-1)^{m-i}\binom{m}i f(x+i)$ is called $m$-th finite difference of $f$. It equals $m!$ times $f^{(m)}(\theta)$ for some $\theta$ between $x$ and $x+m$ (proof: consider the function $g(y)=f(y)-h(y)$, where $h$ is a polynomial of degree at most $m$ taking the same values as $f$ at the points $x+i$, $i=0,\dots,m$. By Rolle's theorem find $\theta$ such that $g^{(m)}(\theta)=0$.) Your conjecture follows taking $f(y)=y^s$ and $x=k$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.